Achieving universal health coverage in sub-Saharan Africa: the role of leadership development - Janet Michel; M Ishaaq Datay; Thabang J Motsohi; Till Bärnighausen; Fabrizio Tediosi; Di McIntyre; Marcel Tanner; David Evans (Inishmore Laser Scientific Publishing Ltd, 2020)
Countries world-wide are striving towards Universal Health Coverage (UHC). Financial resources are extremely limited in developing countries and many developing countries are in the midst of multiple interconnected social, economic, epidemiologic, demographic, technological, institutional, environmental and political transitions. According to the World Health Organization (WHO), accelerating progress towards UHC in Africa will require strong leadership. At the recent Global Conference on Primary Health Care (PHC), the Astana Declaration, the world recommitted to comprehensive Primary Health Care as a keystone of Universal Health Coverage. There is evidence that PHC works. Countries that followed the Alma Ata PHC principles have demonstrated population health outcomes and reduced inequalities at low costs as seen in Chile, Cuba, Ethiopia and Rwanda. What seems to be missing is leadership to apply and uphold these PHC principles. There is consensus that if Astana is to be realized, strong political, economic, education, health, science, institutional, and community leaders are needed to make PHC work this time around. Governments and leaders in Africa have been conveying a constant message, that those leading and managing health systems are not sufficiently prepared to succeed in leadership roles they now occupy. Africa has had different leaders with the same results for decades. Leadership development efforts made to date seem not to be producing desired results. Students taken out of Africa to be trained in leadership at western universities, seem to go back home and carry on as usual. Many students have been taken to the West for education, developed great visions and ideas of how they can transfer knowledge learnt, got home and got swallowed by the system. Pumping more money into a health system with no leadership development will not help us achieve 'Health for All' in sub-Saharan Africa. How can accountable leadership with a sense of consciousness for social justice be developed successfully in these contexts? If leadership is key for Universal Health Coverage to be achieved in sub-Saharan Africa, is it not high time attention is paid to leadership development approaches.